RETRACTED ARTICLE: LDH hybrid thermosensitive hydrogel for intravaginal delivery of anti-HIV drugs. Issue 1 (4th December 2019) - Tian, Wenxue; Han, Shangcong; Huang, Xia; Han, Mei; Cao, Jie; Liang, Yan; Sun, Yong
Abstract : We, the Editors and Publisher of the journal Artificial Cells, Nanomedicine, and Biotechnology, have retracted the following article: Wenxue Tian, Shangcong Han, Xia Huang, Mei Han, Jie Cao, Yan Liang & Yong Sun (2019) LDH hybrid thermosensitive hydrogel for intravaginal delivery of anti-HIV drugs. Artificial Cells, Nanomedicine, and Biotechnology, 47:1, 1234–1240, DOI: 10.1080/21691401.2019.1596935 Since publication, concerns were raised about Figure 3. When approached for an explanation, the authors have been unable to provide a satisfactory response. We are therefore retracting this article and the corresponding author listed in this publication has been informed. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as 'Retracted'.